Analysis of the influence of the application of Kinesio Tape on the muscular activation during an indoor soccer pass - Nuno, Sérgio (2022)
Introduction – Futsal is a demanding sport, so the application of Kinesio tape bands emerges as an intervention hypothesis to take into consideration. Objectives – To analyze Kinesio tape effects on the muscular range and activation of the peroneal muscle and tibialis anterior muscle during the execution of a pass. Methodology – For each specified situation (without and with Kinesio tape band for the tibialis anterior and long peroneal, applied separately), 40 passes were studied, totaling up to 120 distinct behaviors. The technical move was performed by athletes without an injury background. After the evaluation of the electromyographic signal, the two presented peaks were studied. Results – There were differences noted between the three studied situations under study. The Kinesio tape band didn't prove itself to be effective on the anticipation and augment of muscular activation under the conditions defined in the study. Discussion – The executant establishes different strategies to respond to different stats of stability throughout that same task. Conclusion – The individuality of each technical behavior was studied and through the absence of any injury in its executants and through the proposed technical move, the Kinesio tape band's stimulus may not have sufficed to augment muscular activation.